THE UPPER CIBULAKAN SANDSTONE RESERVOIR FACIES ANALYSIS AND CHARACTERIZATION, LARAS FIELD, NORT WEST JAWA BASIN - Kartika Dani S, Priantoro
Laras Field has located in the North West Java Basin. Administratively, this field is part of the Subang Regency. The Field was discovered in 1969 by L-1 exploration well. Hydrocarbon production from the Laras Field began in 1971 with peak production in 1974, reaching 56,000 BOPD from the Upper Cibulakan Formation. This reservoir deposited in a shallow marine environment above the Baturaja Formation. The sandstone reservoir of the Upper Cibulakan Formation in Laras Field consists of several intervals, namely LRS-22, LRS-23, LRS-26, LRS-27, LRS- 29, LRS-33, LRS-34, LRS-35, and LRS-36 with a depth range from 2.200 ft to 3.600 ft. The reservoir layers of LRS-22, LRS-27B, and LRS-29C are the largest hydrocarbon producers in the Laras Field and describe as shallow-marine sandstone reservoirs with a wide reservoir distribution and homogeneous reservoir characters. Both reservoirs have entered the mature category with waterflood programs from 2001 and 2010 in the West Block. The Waterflood program's main problem is that the results of development well drilling are not optimal after the injection process began. The results of drilling development wells indicate that LRS-22, LRS-27B, and LRS-29 have high heterogeneity. Reservoir heterogeneity found in the Laras Field includes changes in facies and rock property characters vertically and laterally. This condition shows previous prediction inaccuracy that the Upper Cibulakan Formation has an extensive geometry and homogeneous rock properties. This research aims to define the Upper Cibulakan Formation sandstone characteristics and reservoir genetic communication, both lateral and vertical, based on integrating 900 ft conventional core data, 74 RCA data, 152 well logs, and three-dimensional seismic data. The sequence stratigraphy method will divide the Upper Cibulakan Formation sandstones in a geological time frame or bounded by chronostratigraphic markers. This method will provide a detailed description of the Upper Cibulakan Formation sandstone reservoirs facies characteristics and each reservoirs facies geometry. Conventional cores analysis shows seven lithofacies in the Upper Cibulakan Formation, namely: claystone-siltstone, lenticular siltstone, flaser sandstones, cross-bedded sandstones, non-calcareous sandstones, laminated – cross lamination sandstone, and calcareous sandstones. The lithofacies arrangement of the Upper Cibulakan Formation in Laras Field is divided into two. The first lithofacies are constituents of tidal shelf ridges that form in shallow marine environments. The second lithofacies is beach barrier deposits from the backshoreforeshore environment. The lithofacies of tidal shelf ridges are siltstone-siltstones, calcareous sandstones, lenticular siltstones, flaser sandstones, cross-bedded sandstones, and non-calcareous sandstones. Laras Field tidal shelf ridges reservoir consists of lenticular siltstone, flaser sandstone, cross-bedded sandstones, and massive sandstones. The lithofacies that forming beach barrier deposits are crosslaminated sandstones and laminated sandstones. This beach barrier deposit only present in the depositional interval of the LRS-22C reservoir. The tidal shelf ridges lithofacies divided into four association facies that reflect the tidal shelf ridge development stages. The four association facies form a cyclic or repetitive pattern bounded by chronostratigraphic markers of marine flooding surfaces. Siltstone-claystone and calcareous sandstones are part of the embryonic phase. Calcareous sandstones from the embryonic stage characterized by an abundance of shell fragments and siltstone-claystone clasts from previously deposited rocks. These sandstones indicate the presence of transgressive surface chronostratigraphic markers. Lenticulars siltstone and flaser sandstones are part of the immature accretion phase, while the mature accretion phase consists of cross-bedded sandstones and non-calcareous sandstones. Calcareous sandstones and claystone are a member of an abandonment phase. These calcareous sandstones show the presence of intensive bioturbation and high cementation. The presence of four associated facies in the deposition of tidal shelf ridges reflects the vertical heterogeneity of facies that compose the reservoirs in the Upper Cibulakan Formation. The geometry of the tidal shelf ridges sandstone reservoir in Laras Field shows sandstone ridges morphology with a northeast-southwest trend. The ridge morphology will control the lateral distribution of associated facies, especially the mature accretion stage. Mature accretion facies generally formed at the thickest part of the tidal shelf ridges due to the influence of waves current during deposition. Immature accretion facies are formed due to tidal currents effect and have a wider distribution. The facies reconstruction analysis using a high-resolution sequence stratigraphic method shows that the sandstones of the Upper Cibulakan Formation are part of the transgressive deposits of the ancient coastline, which are dominated by tidal currents mixed with wave currents. The facies reconstruction analysis using a highresolution sequence stratigraphic method shows that the sandstones of the Upper Cibulakan Formation are part of the transgressive deposits of the ancient coastline, which are dominated by tidal currents mixed with wave currents and storms. Using this method, the analysis result can increase the confidence level in the heterogeneity model of the Upper Cibulakan Formation reservoir in Laras Field. This analysis provides a more accurate description of the Laras field's development and provides benefits during production.